Tubeworms as bioindicators of paleoenvironmental conditions - de Siqueira Tavares, Isabelle; Bosetti, Elvio Pinto; Richter, Kevin William; Comniskey, Jeanninny Carla; Ghilardi, Renato Pirani [UNESP]; Moro, Rosemeri Segecin (Elsevier, 2024)
Tubeworms comprise an informal designation for a biological group of marine invertebrates, associated with producing rigid tubes around their body with varied compositions and functions. The main representatives of this group currently comprise organisms from different phyla and have a wide stratigraphic distribution, taxonomic and biostratigraphic discussions have always been related to the group, not presenting themselves in a distinct way for the Devonian of the Paraná Basin. In the present work, we recognize the taxa Annulitubus mutveii, Cornulites auxilium, and a polychaete agglutinating of the order Terebellida occurring in all lithofacies of the lower shoreface to the offshore from Late Praguian to Givetian. In addition, we discuss the potential of Annulitubus mutveii as a paleoenvironmental bioindicator associated with ecologically stressed environments caused by post-biotic crises caused by extinction events.
Keywords: Bioindicator; Devonian; Paleoenvironmental; Paraná basin; Tubeworms